The Fiqh of Hisab Rukyat of Modernist Mass Organizations: A Study of Muhammadiyah and Al-Irsyad Al-Islamiyah Thought on the Hijri Calendar - Marwadi; Mughni Labib (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This study aims to analyze the differences in the epistemology of rukyat hisab fiqh between two modernist Islamic organizations in Indonesia, namely Muhammadiyah and Al-Irsyad Al-Islamiyah, in determining the beginning of the Hijri month. Both start from the same legal sources, namely the Qur'an and Hadith, but produce different methods and decisions. Muhammadiyah uses the hisab imkanurrukyat method with the Single Global Hijri Calendar (KHGT) model as a representation of contextual ijtihad that emphasizes rationality and global welfare. In contrast, Al-Irsyad Al-Islamiyah adheres to the rukyat method with hisab guidance as technical support, representing textual ijtihad that emphasizes literal adherence to the text. This study uses a qualitative method with an approach to the intellectual and social history of Islamic law. Data were obtained through analysis of documents, fatwas, and decisions of mass organizations related to rukyat hisab. The research results show that these differences are rooted in the epistemological paradigms of each organization: Muhammadiyah tends toward a contextual-rational approach, while Al-Irsyad tends toward a textual-normative approach. Despite their differing approaches, both share the same goal: to establish certainty about prayer times and maintain the unity of the community. This finding confirms that epistemological plurality in determining the Hijri calendar is inevitable in the dynamics of modern Islamic thought.